2017
DOI: 10.1177/1753193417690472
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of the wrist after total wrist arthroplasty

Abstract: Our aim was to assess the outcome in patients with total wrist arthroplasty performed for end stage wrist osteoarthritis. We analysed the ranges of motion of operated and un-operated wrists using a flexible electrogoniometer during the Sollerman hand function test. We assessed grip strength with a digital dynamometer and completed patient reported outcome scores more than one year post-operatively. We reviewed 12 patients with a mean age of 64 (range 48-82) years. The flexion-extension arc was 72% and radiouln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Although other currently Food and Drug Administration‐approved implants have similar ellipsoidal designs for the polyethylene cap, they may reflect different behavior than the implant studied here. We did not directly discuss the ROM between cohorts and their magnitude of relationship to COR due to the small sample size, but similar to previous studies, 50,51 we found a lower ROM for TWA patients relative to the healthy wrists. Furthermore, although the relative alignment of TWA components to the bones might affect the wrist's ROM, we did not see any variations in the COR proximal‐distal shift relative to the extent of ROM.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although other currently Food and Drug Administration‐approved implants have similar ellipsoidal designs for the polyethylene cap, they may reflect different behavior than the implant studied here. We did not directly discuss the ROM between cohorts and their magnitude of relationship to COR due to the small sample size, but similar to previous studies, 50,51 we found a lower ROM for TWA patients relative to the healthy wrists. Furthermore, although the relative alignment of TWA components to the bones might affect the wrist's ROM, we did not see any variations in the COR proximal‐distal shift relative to the extent of ROM.…”
Section: Discussionsupporting
confidence: 69%
“…This COR shift was roughly two times more for the TWA when compared to that for a healthy wrist (17.1 mm compared to 7.2 mm) illustrating a significant mismatch in kinematics. Previous studies [48][49][50][51] have shown the dissimilarity in ROM and pattern of stress distribution between healthy and replaced wrists, which could be the result of this mismatch in COR. In this study, the calculated healthy wrist's COR was similar to previous studies that have reported the COR location at the proximal pole of capitate with 5 to 10 mm distal shift.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the Maestro TM Total Wrist achieves the most favorable functional outcome as compared to other third-generation types, and it may be justified in preserving resection-related carpal height due to its 3 various carpal heads in combination with its design of ellipsoid surface articulation especially in order to avoid radial impingement that is mainly observed with the use of the ReMotion TM Total Wrist with its in contrast to both MaestroTM types straight design of carpal plate (Figure 1A-C, Figure 3, Figure 11A-E) [32,46,70]. However, none of all third generation TWAs are able to restore completely motion in the anatomic axes of a normal wrist including the "dart-throwing" motion arc from extension-radial deviation to flexion-ulnar deviation [71][72][73]. This motion arc that is performed in an oblique axis at the midcarpal joint is particularly prevalent in most occupational, recreational and avocational activities such as hammering, clubbing or fly fishing; whereas the so-called "reversed dart-throwing" motion arc from extension-ulnar deviation to flexionradial deviation takes place almost exclusively at the radiocarpal joint [15,74].…”
mentioning
confidence: 99%
“…RMSE translations are reported for the components of radioulnar (RU), volar/dorsal (VD), and proximal/distal (PD). studies on TWA have used electrogoniometers and OMC systems to evaluate the overall wrist range-of-motion after TWA [28,29]; however, these techniques have a high cross-talk error (up to 5 deg) or soft-tissue artifact [23,30]. Here, we demonstrated the BVR's high accuracy in calculating the kinematics of the TWA; hence, investigators may be able to achieve much higher accuracy in studying TWA kinematics in vivo using BVR.…”
Section: Discussionmentioning
confidence: 73%